2008
DOI: 10.1115/1.2813005
|View full text |Cite
|
Sign up to set email alerts
|

Time Resolved Experimental Investigations of an Axial Compressor With Casing Treatment

Abstract: A casing treatment with axial and radial skewed slots ending in a plenum chamber has experimentally been investigated at a highly subsonic axial compressor stage. The aim was to investigate the physical phenomenon of this treatment family that is responsible for the stabilization of the blade passage flow and the drop in efficiency mostly observed. The experimentally gained performance results of this configuration showed an extension of the operating range by approximately 50%, while the efficiency for design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…For the researches about the casing treatment, most of them focus on the overall performance to improve the stall margin and reduce the efficiency penalty by testing different forms of casing treatment, which includes circumferential groove [11][12][13], skewed slot with different shapes [11][12][13][14][15], self-recirculating casing treatment [16], SPS casing treatment [17]. On the other hand, some researches pay attention to the influence of casing treatment on detailed flow field, trying to explain how casing treatment delays the stall [18][19][20]. These studies indicate that the casing treatment can delay the occurrence of instability inception by inducing a recirculating path to reduce flow blockage at rotor tip.…”
Section: Introductionmentioning
confidence: 99%
“…For the researches about the casing treatment, most of them focus on the overall performance to improve the stall margin and reduce the efficiency penalty by testing different forms of casing treatment, which includes circumferential groove [11][12][13], skewed slot with different shapes [11][12][13][14][15], self-recirculating casing treatment [16], SPS casing treatment [17]. On the other hand, some researches pay attention to the influence of casing treatment on detailed flow field, trying to explain how casing treatment delays the stall [18][19][20]. These studies indicate that the casing treatment can delay the occurrence of instability inception by inducing a recirculating path to reduce flow blockage at rotor tip.…”
Section: Introductionmentioning
confidence: 99%
“…axial slots which are skewed to the radial direction) has been studied by a number of researchers. [11][12][13][14][15][16][17] Greitzer et al 11 carried out experiments to investigate the effect of axial slots on the performance of two compressor rotor builds having different solidities. It was found that endwall casing treatment is only beneficial to the so called ''wall-stall'' compressor rotors, in which stall is initiated on the annulus wall.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that the effect of slots is the repositioning of the tip clearance vortex trajectory toward the trailing-edge of the blade passage and delaying the movement of the incoming-tip clearance flow interface to the leading-edge plane. Emmrich et al 16 experimentally investigated axial and radial skewed slots in a highly subsonic compressor stage. Approximately 50% operating range extension was obtained at the expense of about 1.4% reduction in the compressor efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…This will allow higher thrust-to-weight ratios to be achieved, which is one of the main objectives of the aeroengine designers. Compact design of compressors means to reduce the number of stages, which in turn is associated with imposing more aerodynamic loads on each stage [1]. On the other hand, to consider tip clearances for the blades is inescapable.…”
Section: Introductionmentioning
confidence: 99%